Hepatocarcinoma in a Patient with Alpha-1 Antitrypsin Deficiency: A Case Report - Leite, Renata (2023)
Alpha-1 antitrypsin deficiency is an autosomal recessive genetic disorder in which there are deficiency alleles at the protease inhibitor (Pi) locus, located on the long arm of chromosome 14. Among all the variants related to clinical disease, the Z mutation is the most common and derives from the substitution of glutamic acid for lysine at position 342 of the SERPINA1 gene. In the liver, accumulation of the mutant protein in hepatocytes can lead to neonatal cholestasis, chronic liver disease, liver cirrhosis, and hepatocellular carcinoma. The diagnosis of the disease requires, in addition to measuring serum levels of alpha-1 antitrypsin, recognition of the clinical pattern, physical examination, family history, identification and interpretation of test results with phenotyping/genotyping. The report aims to address the case of a patient with alpha-1 antitrypsin deficiency who developed liver cirrhosis hepatocellular carcinoma identified in the liver explant, as well as to discuss the laboratory, clinical, imaging and histological findings, identifying the repercussion of the disease in individuals, complications and the best diagnostic and therapeutic approach.